2020
DOI: 10.1007/s00228-019-02818-7
|View full text |Cite
|
Sign up to set email alerts
|

Individual factors increasing complexity of drug treatment—a narrative review

Abstract: Purpose Complexity of drug treatment is known to be a risk factor for administration errors and nonadherence promoting higher healthcare costs, hospital admissions and increased mortality. Number of drugs and dose frequency are parameters often used to assess complexity related to the medication regimen. However, factors resulting from complex processes of care or arising from patient characteristics are only sporadically analyzed. Hence, the objective of this review is to give a comprehensive overview of rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 87 publications
1
15
0
Order By: Relevance
“…In another study Schmidt et al identified the demographic and clinical factors that resulted in more frequent patient non-compliance with medical advice. As in our study, the existence of numerous comorbidities was one reason for patients' less frequent use of medications [17].…”
Section: Discussionsupporting
confidence: 60%
“…In another study Schmidt et al identified the demographic and clinical factors that resulted in more frequent patient non-compliance with medical advice. As in our study, the existence of numerous comorbidities was one reason for patients' less frequent use of medications [17].…”
Section: Discussionsupporting
confidence: 60%
“…To do so, we combined a literature-based with a qualitative approach. As described previously by our group, 91 complexity factors were identified [1] which had to be rated for their relevance by experts to decide upon their inclusion in the tool. We therefore formed an expert panel of 10 experts (clinical pharmacologists, general practitioners, and pharmacists involved in the development of the electronic tool and their colleagues) to rate factors previously characterised in the literature as having little relevance (1 point), medium relevance (2 points), and high relevance (3 points).…”
Section: Automated Assessment Of Complexity Factorsmentioning
confidence: 99%
“…Out of the 91 factors increasing treatment complexity [1] 34 complexity factors were excluded due to a low relevance according to the expert panel. Four complexity factors were additionally included based on expert opinion, i.e.…”
Section: Automated Assessment Of Complexity Factorsmentioning
confidence: 99%
See 2 more Smart Citations